Hydrolysis acidification wastewater treatment process for strengthening extracellular electron transfer

By setting up carbon fiber suspension filler and wire mesh frame in the hydrolysis and acidification reactor, a micro current environment is built and the conductive is enhanced using coating solution, the problems of low H2 solubility and difficulty in degrading organic matter treatment are solved, and efficient wastewater treatment is achieved .

CN119461657AActive Publication Date: 2025-02-18HEFEI UNIV OF TECH +1

Patent Information

Application Number
CN202510045110.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-02-18
Estimated Expiration
2045-01-13

AI Technical Summary

Technical Problem

During the hydrolysis and acidification process, the low solubility of H2 limits the electron transfer rate, and when treating organic matter containing heterocyclic or multi-ring structures, the degradation difficulty increases, and wastewater treatment is complicated.

Method used

采用强化胞外电子传递的水解酸化废水处理工艺,通过在水解酸化反应器中设置碳纤维悬挂填料作为阳极和钢丝网框架作为阴极,构建微电流环境,促进微生物的富集与生长,并通过涂覆溶液增强导电性和光催化性能。

Benefits of technology

It significantly improves the efficiency of the hydrolysis and acidification process, improves the decomposition efficiency of difficult-to-degrade organic matter, enhances the overall efficiency of wastewater treatment, and extends the operating cycle of the treatment system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461657A_ABST
    Figure CN119461657A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of wastewater treatment, in particular to a hydrolytic acidification wastewater treatment process for strengthening extracellular electron transfer, which comprises the following steps: S1, constructing a hydrolytic acidification reactor, taking carbon fiber suspension filler as an anode, taking a steel wire mesh frame as a cathode, connecting the carbon fiber suspension filler in series by a stainless steel wire rope, and taking the stainless steel wire rope as a cathode; the carbon fiber suspension filler is connected with the steel wire mesh frame through an electrochemical workstation; s2, inoculating hydrolytic acidification bacteria into a reactor, controlling culture conditions, and domesticating microorganisms in a micro-current environment until a biological membrane is formed on the carbon fiber suspension filler; s3, inputting wastewater to be treated into the reactor, controlling treatment conditions, monitoring an effluent result, and discharging after the effluent result reaches the standard. Compared with traditional interspecific electron transfer, the wastewater treatment method has higher efficiency and speed, the oxygenolysis process of organic matter is accelerated, and the overall efficiency of wastewater treatment is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wastewater treatment, and in particular to a hydrolysis-acidification wastewater treatment process that strengthens extracellular electron transfer. Background Art

[0002] As a pre-treatment step for many biological treatment processes (such as aerobic processes), hydrolysis and acidification technology not only lays a solid foundation for subsequent biochemical treatment, but also shows good performance in treating wastewaters with extremely high treatment difficulty, such as pharmaceutical wastewater, printing and dyeing wastewater, papermaking wastewater, and petrochemical wastewater. The core of hydrolysis and acidification technology is that it utilizes the metabolic characteristics of anaerobic microorganisms. In an oxygen-deficient environment, these microorganisms gradually convert long-chain hydrocarbons, aromatic compounds and other macromolecular organic matter into easily biodegradable fatty acids, alcohols, amino acids and other small molecules through a series of complex biochemical reactions. This process significantly reduces the biological toxicity of wastewater and greatly improves the biodegradability of wastewater, making the originally difficult-to-treat wastewater easier to be accepted and degraded by subsequent biological treatment processes. In addition, the hydrolysis and acidification process is accompanied by the removal of some organic matter, which further reduces the burden on subsequent treatment units, provides them with more stable and high-quality water inlet conditions, and improves the treatment efficiency of the entire wastewater treatment system.

[0003] In the hydrolytic acidification process, the hydrolytic acidification bacteria involved in substrate oxidation usually rely on H 2 As an electron carrier, H transfers the generated electrons to organic pollutants to achieve the reduction of their functional groups. 2 The low solubility in water severely limits the speed of electron transfer, becoming one of the key factors restricting the efficiency of hydrolysis and acidification. In addition, the degradation difficulty of hydrolysis and acidification bacteria increases significantly when dealing with organic matter containing a large number of heterocyclic or polycyclic structures. The presence of these complex organic matter further exacerbates the complexity of wastewater treatment. Summary of the invention

[0004] In order to solve the problems mentioned in the above background technology, the present invention provides a hydrolysis acidification wastewater treatment process for enhancing extracellular electron transfer.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions: A hydrolysis acidification wastewater treatment process for strengthening extracellular electron transfer comprises the following steps: S1. Construct a hydrolysis acidification reactor, wherein the hydrolysis acidification reactor comprises a carbon fiber suspension filler arranged inside the reactor and a steel wire mesh frame floating on the water surface, wherein the carbon fiber suspension filler serves as an anode and the steel wire mesh frame serves as a cathode, wherein the carbon fiber suspension filler is connected in series by stainless steel wire ropes as a whole, wherein the spacing between the upper and lower carbon fiber suspension fillers is 50-80 mm, forming several groups of modular fillers, which are stacked inside the reactor to form a modular structure, wherein the carbon fiber suspension filler is connected to the steel wire mesh frame through an electrochemical workstation, and the carbon fiber filler is connected to the electrochemical workstation through a copper wire to form a closed circuit; S2. Inoculate the hydrolytic acidifying bacteria in the existing biological treatment system into the reactor, control the culture conditions, promote the growth of microorganisms, and culture and domesticate the microorganisms in a microcurrent environment until a biofilm is formed on the carbon fiber suspension filler; S3. Input the wastewater to be treated into the reactor, control the treatment conditions, monitor the effluent results, and discharge it after it meets the standards.

[0006] Furthermore, the carbon fiber suspension filler in step S1 is prepared by the following steps: Select carbon fiber filaments with a diameter of 0.5-1.0 mm, clean the carbon fiber filaments with an ultrasonic cleaner for 5-10 minutes at a power of 50-100 W, then soak and clean them with anhydrous ethanol for 20-30 minutes, and then soak them in a hydrogen peroxide solution for activation, take them out and dry them to obtain pretreated carbon fiber filaments, immerse the pretreated carbon fiber filaments in a coating solution and let them stand or gently stir the solution several times for 10-20 minutes, take out the carbon fiber filaments, absorb excess coating solution with filter paper, hang them in an oven, heat them to 100-110°C, dry them for 2-4 hours until the coating layer is solidified, and cool them to obtain carbon fiber suspension fillers.

[0007] Furthermore, the culture conditions in step S2 are specifically as follows: temperature is 30±2°C, pH value is 6.5-7.5, and C:N:P is maintained at 100:(5-5.5):(1-1.2).

[0008] Furthermore, in step S2, the microcurrent environment is specifically as follows: the initial current is 1 mA, which gradually increases by 0.08-0.12 mA every 2 days until the final current is 5-5.4 mA, and the total acclimation period is no less than 30 days.

[0009] Furthermore, the hydrolytic acidifying bacteria include one or more of Brevibacillus faecalis, Acetobacter, Bacillus lysinicus, Brevibacterium rosea, Serratia, and Bacillus licheniformis.

[0010] Furthermore, the processing conditions in step S3 are as follows: the water flow rate is 0.4-0.6m 3 / h, maintain the hydraulic retention time at 18-24h, and adjust the current to 3-7mA through the electrochemical workstation.

[0011] Furthermore, the concentration of the hydrogen peroxide solution is 0.1-0.3 mol / L, the activation temperature is 60-70° C., and the activation time is 1-2 h.

[0012] Further, the coating solution comprises the following steps to prepare: A1. In a reactor equipped with a constant pressure dropping funnel, a reflux condenser and a nitrogen protection device, add iodine and a magnesium strip, add hexyl bromide dropwise, keep the reaction solution slightly boiling, and after the addition is completed, obtain a reaction solution, add thiophene to anhydrous ethanol to obtain a thiophene solution, slowly drop the thiophene solution into the reaction solution, react for 24 hours after the addition is completed, and after the reaction is completed, hydrolyze the reaction mixture with a saturated ammonium chloride solution, separate the organic layer, dry it with anhydrous sodium sulfate, and collect 3-hexylthiophene by distillation; A2, 3-hexylthiophene and potassium polymetaphosphate were added to a reactor pre-filled with toluene solvent, and stirred and dissolved under nitrogen protection until completely transparent, azobisisobutyronitrile and butylated hydroxyanisole were added, the reactor was sealed, and the reactor was placed in an oil bath, heated to 70-80°C, and reacted for 24-36h. After the reaction was completed, the mixture was cooled to room temperature, poured into methanol for precipitation, and filtered to obtain a copolymer precipitate; A3. Add the copolymer to N,N-dimethylformamide, stir until dissolved, add nano titanium dioxide powder, use ultrasonic disperser for 20-30 minutes to evenly disperse, stir for 1-2 hours under magnetic stirring, filter, wash, place in a 60°C vacuum oven to dry to constant weight, and re-formulate with N,N-dimethylformamide to a coating solution with a concentration of 40-50%.

[0013] Furthermore, in step A1, the mass ratio of elemental iodine, magnesium rod, hexyl bromide, thiophene and anhydrous ethanol is (0.2-0.3):(6.2-6.8):(50-52):(27.5-29):200.

[0014] Furthermore, in step A2, the mass ratio of 3-hexylthiophene, potassium polymetaphosphate, toluene, azobisisobutyronitrile and butylated hydroxyanisole is (20-21.5):(12-14):100:(0.1-0.3):(0.05-0.07).

[0015] Furthermore, in step A3, the mass ratio of the copolymer, N,N-dimethylformamide, and nano-titanium dioxide powder is (10-11):50:(2-2.5).

[0016] Beneficial effects of the present invention: 1. The present invention provides sufficient attachment surface for microorganisms by arranging vertically suspended carbon fiber fillers inside the hydrolysis acidification reactor, which is conducive to the rapid formation and stable maintenance of biofilms. In addition, the carbon fiber fillers serve as anodes to construct a microcurrent environment in the reactor, which can selectively promote the enrichment and growth of conductive or electrophilic microorganisms. These microorganisms have higher efficiency in the decomposition of difficult-to-degrade organic matter, thereby significantly improving the efficiency of the hydrolysis acidification process. In the constructed biological micro-electrolysis reaction system, microorganisms can use redox proteins (especially cytochromes) on the cell membrane and conductive pili and other structures to achieve direct electron transfer with the electrode, which has higher efficiency and speed than traditional interspecies electron transfer (such as through intermediaries), which helps to accelerate the oxidative decomposition process of organic matter and improve the overall efficiency of wastewater treatment.

[0017] 2. In the technical solution of the present invention, the coating solution shows a high degree of order and functionality. The chain structure formed by the copolymerization reaction of 3-hexylthiophene and potassium polymetaphosphate forms a continuous conductive channel, and also provides a stable environment for the attachment of microorganisms through the hydrophobic properties of the hexyl chain. At the same time, the uniform dispersion of nano-titanium dioxide particles in the coating solution further enhances the conductivity and photocatalytic properties of the coating layer, so that the coating layer forms a dense and functional interface layer on the surface of the carbon fiber, which greatly optimizes the interaction between the microorganisms and the electrode. The enhanced conductivity of the copolymer and the semiconductor properties of nano-titanium dioxide jointly promote the efficiency of electron transfer between microorganisms and electrodes, making the electron flow in the wastewater treatment process smoother, thereby improving the overall efficiency of wastewater treatment. Secondly, the photocatalytic performance and antibacterial effect of nano-titanium dioxide effectively inhibit the excessive growth of microorganisms, maintain the activity and stability of the biofilm, extend the operation cycle of the wastewater treatment system, and improve the stability and reliability of the system. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0019] Figure 1 It is a structural schematic diagram of the hydrolysis acidification reactor of the present invention; In the figure: 1. Floating cathode; 2. Electrochemical workstation; 3. Water outlet pipe; 4. Carbon fiber suspension filler; 5. Overflow pipe; 6. Sampling tube; 7. Water inlet pump; 8. Mud discharge pipe. DETAILED DESCRIPTION

[0020] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] Unless otherwise specified, the raw materials used in the present invention are all from conventional products purchased on the market. The hydrolytic acidifying bacteria were cultured using the method described in Shao Ruying, Gao Feng, Zhang Ling, et al. Screening and application research of high-efficiency hydrolytic acidifying bacteria [J]. Guangdong Chemical Industry, 2022, 6 (49): 67-69.

[0022] Preparation Example 1: The coating solution is prepared by the following steps: A1. In a reactor equipped with a constant pressure dropping funnel, a reflux condenser and a nitrogen protection device, 2 g of iodine and 62 g of magnesium strips were added, and 500 g of hexyl bromide was added dropwise, and the reaction solution was kept slightly boiling. After the addition was completed, a reaction solution was obtained, 275 g of thiophene was added to 2000 g of anhydrous ethanol to obtain a thiophene solution, and the thiophene solution was slowly added dropwise to the reaction solution. After the addition was completed, the reaction mixture was reacted for 24 hours. After the reaction was completed, the reaction mixture was hydrolyzed with a saturated ammonium chloride solution, the organic layer was separated, and after drying with anhydrous sodium sulfate, 3-hexylthiophene was collected by distillation; A2, 200g3-hexylthiophene and 120g potassium polymetaphosphate are added to a reactor pre-equipped with 1000g toluene solvent, under nitrogen protection, stirred and dissolved until completely transparent, 1g azobisisobutyronitrile and 0.5g butylated hydroxyanisole are added, the reactor is sealed, the reactor is placed in an oil bath, the temperature is raised to 70°C, the reaction is reacted for 24h, and when the reaction is finished, it is cooled to room temperature, poured into methanol and precipitated, and the copolymer precipitate is obtained by filtration; A3. Add 100g of the copolymer to 500g of N,N-dimethylformamide, stir until dissolved, add 20g of nano titanium dioxide powder, use an ultrasonic disperser to ultrasonicate for 20min until uniformly dispersed, stir under magnetic stirring for 1h, filter, wash, place in a vacuum oven at 60℃ to dry to constant weight, and re-formulate with N,N-dimethylformamide to a coating solution with a concentration of 40%.

[0023] The carbon fiber suspension filler is prepared by the following steps: Select carbon fiber filaments with a diameter of 0.5 mm, clean the carbon fiber filaments with an ultrasonic cleaner for 5 minutes at a power of 50 W, then soak and clean them with anhydrous ethanol for 20 minutes, and then soak them in a hydrogen peroxide solution with a concentration of 0.1 mol / L for activation for 1 hour at a temperature of 60°C. Take them out and dry them to obtain pretreated carbon fiber filaments, immerse the pretreated carbon fiber filaments in the above-prepared coating solution and let them stand for 10 minutes. Take out the carbon fiber filaments, gently absorb the excess coating solution with filter paper, hang them in an oven, raise the temperature to 100°C, and dry them for 2 hours until the coating layer is solidified. After cooling, carbon fiber suspension filler is obtained.

[0024] Preparation Example 2: The coating solution is prepared by the following steps: A1. In a reactor equipped with a constant pressure dropping funnel, a reflux condenser and a nitrogen protection device, 2.5 g of iodine and 65 g of magnesium strips were added, and 510 g of hexyl bromide was added dropwise, and the reaction solution was kept slightly boiling. After the addition was completed, a reaction solution was obtained, 282 g of thiophene was added to 2000 g of anhydrous ethanol to obtain a thiophene solution, and the thiophene solution was slowly added dropwise to the reaction solution. After the addition was completed, the reaction mixture was reacted for 24 hours. After the reaction was completed, the reaction mixture was hydrolyzed with a saturated ammonium chloride solution, the organic layer was separated, and after drying with anhydrous sodium sulfate, 3-hexylthiophene was collected by distillation; A2, 210g3-hexylthiophene and 130g potassium polymetaphosphate are added to a reactor pre-equipped with 1000g toluene solvent, under nitrogen protection, stirred and dissolved until completely transparent, 2g azobisisobutyronitrile and 0.6g butylated hydroxyanisole are added, the reactor is sealed, the reactor is placed in an oil bath, the temperature is raised to 75°C, the reaction is carried out for 30h, and after the reaction is finished, it is cooled to room temperature, poured into methanol and precipitated, and the copolymer precipitate is obtained by filtration; A3. Add 105g of the copolymer to 500g of N,N-dimethylformamide, stir until dissolved, add 22.5g of nano titanium dioxide powder, use an ultrasonic disperser to ultrasonicate for 25min until uniformly dispersed, stir under magnetic stirring for 1.5h, filter, wash, place in a vacuum oven at 60℃ to dry to constant weight, and re-formulate with N,N-dimethylformamide to a coating solution with a concentration of 45%.

[0025] The carbon fiber suspension filler is prepared by the following steps: Select carbon fiber filaments with a diameter of 0.8 mm, clean the carbon fiber filaments with an ultrasonic cleaner for 8 minutes at a power of 60 W, then soak and clean them with anhydrous ethanol for 25 minutes, and then soak them in a hydrogen peroxide solution with a concentration of 0.15 mol / L for activation for 1.5 hours at a temperature of 63°C. Take them out and dry them to obtain pretreated carbon fiber filaments, immerse the pretreated carbon fiber filaments in the coating solution and let them stand or gently stir the solution several times for 15 minutes, take out the carbon fiber filaments, gently absorb the excess coating solution with filter paper, hang them in an oven, raise the temperature to 105°C, and dry them for 3 hours until the coating layer is solidified. After cooling, carbon fiber suspension filler is obtained.

[0026] Preparation Example 3: The coating solution is prepared by the following steps: A1. In a reactor equipped with a constant pressure dropping funnel, a reflux condenser and a nitrogen protection device, 3 g of iodine and 68 g of magnesium strips were added, and 520 g of hexyl bromide was added dropwise, and the reaction solution was kept slightly boiling. After the addition was completed, a reaction solution was obtained, 290 g of thiophene was added to 2000 g of anhydrous ethanol to obtain a thiophene solution, and the thiophene solution was slowly added dropwise to the reaction solution. After the addition was completed, the reaction mixture was reacted for 24 hours. After the reaction was completed, the reaction mixture was hydrolyzed with a saturated ammonium chloride solution, the organic layer was separated, and after drying with anhydrous sodium sulfate, 3-hexylthiophene was collected by distillation; A2, 215g3-hexylthiophene and 140g potassium polymetaphosphate were added to a reactor pre-equipped with 1000g toluene solvent, and stirred and dissolved under nitrogen protection until completely transparent, 3g azobisisobutyronitrile and 0.7g butylated hydroxyanisole were added, the reactor was sealed, and the reactor was placed in an oil bath, heated to 80°C, and reacted for 36h. When the reaction was completed, it was cooled to room temperature, poured into methanol and precipitated, and the copolymer was filtered to obtain a precipitate; A3. Add 110g of the copolymer to 500g of N,N-dimethylformamide, stir until dissolved, add 25g of nano titanium dioxide powder, use an ultrasonic disperser to ultrasonicate for 30min until uniformly dispersed, stir under magnetic stirring for 2h, filter, wash, place in a vacuum oven at 60℃ to dry to constant weight, and re-formulate with N,N-dimethylformamide to a coating solution with a concentration of 50%.

[0027] The carbon fiber suspension filler is prepared by the following steps: Select carbon fiber filaments with a diameter of 1.0 mm, clean the carbon fiber filaments with an ultrasonic cleaner for 10 minutes at a power of 100 W, then soak and clean them with anhydrous ethanol for 30 minutes, and then soak them in a hydrogen peroxide solution with a concentration of 0.3 mol / L for activation for 2 hours at a temperature of 70°C. Take them out and dry them to obtain pretreated carbon fiber filaments, immerse the pretreated carbon fiber filaments in the coating solution and let them stand or gently stir the solution several times for 20 minutes, take out the carbon fiber filaments, gently absorb the excess coating solution with filter paper, hang them in an oven, raise the temperature to 110°C, and dry them for 4 hours until the coating layer is solidified. After cooling, carbon fiber suspension filler is obtained.

[0028] Example 1: A hydrolysis acidification wastewater treatment process for enhancing extracellular electron transfer, comprising the following steps: S1. Construct a 2m×1m×2m hydrolysis acidification reactor, use the carbon fiber suspension filler prepared in Preparation Example 1 as the anode, and the wire mesh frame as the cathode. The carbon fiber suspension filler is connected in series by stainless steel wire ropes as a whole, and the upper and lower carbon fiber suspension fillers are spaced 50 mm apart to form 8 groups of modular fillers, which are stacked inside the reactor to form a modular structure. The carbon fiber suspension filler is connected to the wire mesh frame through an electrochemical workstation, and the carbon fiber filler is connected to the electrochemical workstation through a copper wire to form a closed circuit. S2. Inoculate the hydrolytic acidifying bacteria in the existing biological treatment system into the reactor, culture at a temperature of 28°C and a pH value of 6.5, and add glucose, NH 4 Cl and KH 2 PO 4 , keeping C:N:P at 100:5:1, the microorganisms were cultured and domesticated in a microcurrent environment, the initial current was set to 1 mA, and gradually increased by 0.08 mA every 2 days to a final current of 5 mA, until a stable and highly active biofilm was formed on the carbon fiber suspension filler; S3, input the wastewater to be treated into the reactor, and control the water flow rate to 0.4m 3 / h, maintain the hydraulic retention time at 18h, adjust the current to 3mA through the electrochemical workstation, monitor the effluent results, and discharge after meeting the standards.

[0029] Example 2: A hydrolysis acidification wastewater treatment process for enhancing extracellular electron transfer, comprising the following steps: S1. Construct a 2m×1m×2m hydrolysis acidification reactor, use the carbon fiber suspension filler prepared in Preparation Example 2 as the anode, and the steel wire mesh frame as the cathode. The carbon fiber suspension filler is connected in series by stainless steel wire ropes as a whole, and the spacing between the upper and lower carbon fiber suspension fillers is 65mm, forming 8 groups of modular fillers, which are stacked inside the reactor to form a modular structure. The carbon fiber suspension filler is connected to the steel wire mesh frame through an electrochemical workstation, and the carbon fiber filler is connected to the electrochemical workstation through a copper wire to form a closed circuit; S2. Inoculate the hydrolytic acidifying bacteria in the existing biological treatment system into the reactor, culture at a temperature of 30°C and a pH value of 7.0, and add glucose, NH 4 Cl and KH 2 PO 4 , keeping C:N:P at 100:5.2:1.1, the microorganisms were cultured and domesticated in a microcurrent environment, the initial current was set to 1 mA, and gradually increased by 0.1 mA every 2 days to a final current of 5.2 mA, until a stable and highly active biofilm was formed on the carbon fiber suspension filler; S3, input the wastewater to be treated into the reactor, and control the water flow rate to 0.5m 3 / h, maintain the hydraulic retention time at 21h, adjust the current to 5mA through the electrochemical workstation, monitor the effluent results, and discharge after meeting the standards.

[0030] Example 3: A hydrolysis acidification wastewater treatment process for enhancing extracellular electron transfer, comprising the following steps: S1. Construct a 2m×1m×2m hydrolysis acidification reactor, use the carbon fiber suspension filler prepared in Preparation Example 3 as the anode, and the wire mesh frame as the cathode. The carbon fiber suspension filler is connected in series by stainless steel wire ropes as a whole, and the spacing between the upper and lower carbon fiber suspension fillers is 80mm, forming 6 groups of modular fillers, which are stacked inside the reactor to form a modular structure. The carbon fiber suspension filler is connected to the wire mesh frame through an electrochemical workstation, and the carbon fiber filler is connected to the electrochemical workstation through a copper wire to form a closed circuit; S2. Inoculate the hydrolytic acidifying bacteria in the existing biological treatment system into the reactor, culture it at a temperature of 32°C and a pH value of 7.5, and add glucose, NH 4 Cl and KH 2 PO 4 , keeping C:N:P at 100:5.5:1.2, the microorganisms were cultured and domesticated in a microcurrent environment, the initial current was set to 1 mA, and gradually increased by 0.11 mA every 2 days to a final current of 5.4 mA, until a stable and highly active biofilm was formed on the carbon fiber suspension filler; S3, input the wastewater to be treated into the reactor, and control the water flow rate to 0.6m 3 / h, maintain the hydraulic retention time at 24h, adjust the current to 7mA through the electrochemical workstation, monitor the effluent results, and discharge after meeting the standards.

[0031] Comparative Example 1: The difference between this comparative example and Preparation Example 1 is that 3-hexylthiophene is not added in step A1, and the remaining steps are the same as those in Preparation Example 1.

[0032] Comparative Example 2: The difference between this comparative example and Preparation Example 2 is that potassium polymetaphosphate is not added in step A2, and the remaining steps are the same as Preparation Example 2.

[0033] Comparative Example 3: The difference between this comparative example and Preparation Example 3 is that no nano titanium dioxide powder is added in step A3, and the remaining steps are the same as Preparation Example 3.

[0034] Comparative Example 4: The difference between this comparative example and Example 1 is that the coating solution prepared in Comparative Example 1 is used, and the remaining steps are the same as those in Example 1.

[0035] Comparative Example 5: The difference between this comparative example and Example 2 is that the coating solution prepared in Comparative Example 2 is used, and the remaining steps are the same as those in Example 2.

[0036] Comparative Example 6: The difference between this comparative example and Example 3 is that the coating solution prepared in Comparative Example 3 is used, and the remaining steps are the same as those in Example 3.

[0037] Comparative Example 7: The difference between this comparative example and Example 1 is that biochar is used as the anode, and the remaining steps are the same as Example 1.

[0038] Comparative Example 8: The difference between this comparative example and Example 2 is that activated carbon fiber is used as the anode, and the remaining steps are the same as Example 2. The specific surface area of ​​the activated carbon fiber (ACF) is 2000m 2 / g, and the volume of micropores accounts for more than 90% of the total pore volume.

[0039] A wastewater sample from a coking plant was evenly divided into 8 parts and treated by the treatment processes of Examples 1-3 and Comparative Examples 4-8 respectively. The five-day biochemical oxygen demand (BOD5), chemical oxygen demand (COD) and ammonia nitrogen index in the effluent were monitored, and the COD removal rate and BOD5 removal rate of each embodiment and comparative example were calculated. The results are shown in Table 1 and Table 2: Table 1. Wastewater treatment results of Examples 1-3 and Comparative Examples 4-8 Table 2. COD removal rate and BOD5 removal rate results of Examples 1-3 and Comparative Examples 4-8

[0040]

[0041] According to the definition of unit volume removal load in GB / T 41017-2021 "Guidelines for Water Reuse - Wastewater Regeneration Treatment Technology and Process Evaluation Method", the unit volume removal loads of BOD5, COD, and ammonia nitrogen of Examples 1-3 and Comparative Examples 4-8 (mg / m 3 h), the results are shown in Table 3: Table 3. Unit volume load removal results of Examples 1-3 and Comparative Examples 4-8

[0042]

[0043] It can be seen from Table 1, Table 2 and Table 3 that the removal rates of BOD5, COD and ammonia nitrogen in Examples 1-3 are higher than those in Comparative Examples 4-8, and the removal load per unit volume of Examples 1-3 is also higher than that in Comparative Examples 4-8. 3 / h-0.6m 3 / h), the BOD5 and COD removal rates of Examples 1-3 were slightly improved, but the ammonia nitrogen removal rate remained relatively stable, and the removal load per unit volume also increased with the increase of the influent flow rate, indicating that at a higher flow rate, the reactor can treat more pollutants.

[0044] In Comparative Example 4, 3-hexylthiophene was not added in step A1, which may affect the performance of the coating solution, thereby affecting the performance of the anode and the attachment of microorganisms. In Comparative Example 5, potassium polymetaphosphate was not added in step A2, and in Comparative Example 6, nano titanium dioxide powder was not added in step A3, which may affect the formation and performance of the copolymer and the dispersibility and stability of the coating solution, thereby affecting the stability and conductivity of the anode.

[0045] Comparative Examples 7 and 8 use biochar and activated carbon fiber as anodes, respectively, which may have different conductivity, specific surface area and microbial attachment performance compared with carbon fiber suspension fillers. The removal rates and unit volume removal loads of Comparative Examples 7 and 8 are lower than those of Examples 1 and 2, indicating that carbon fiber suspension fillers have better performance as anodes in wastewater treatment.

[0046] In Examples 1-3, as the current increased and the hydraulic retention time prolonged, the removal rate and the removal load per unit volume increased, probably because the higher current promoted the extracellular electron transfer and metabolic activities of the microorganisms, while the longer hydraulic retention time allowed the microorganisms more time to degrade the pollutants.

[0047] In summary, by controlling the feed ratio of each raw material in the preparation of carbon fiber suspension filler and optimizing the parameters in wastewater treatment, the wastewater treatment methods of Examples 1-3 are significantly better than those of Comparative Examples 4-8, indicating that the wastewater treatment method of the present invention can improve the overall efficiency of wastewater treatment.

[0048] In the description of the specification, the description with reference to the terms "embodiment", "various embodiments" and the like means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or preparation example are included in at least one embodiment or preparation example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or preparation example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or preparation examples in a suitable manner.

[0049] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A hydrolysis acidification wastewater treatment process for strengthening extracellular electron transfer, characterized in that: The following steps are involved: S1. Construct a hydrolysis acidification reactor, wherein the hydrolysis acidification reactor comprises a carbon fiber suspension filler arranged inside the reactor and a steel wire mesh frame floating on the water surface, wherein the carbon fiber suspension filler serves as an anode and the steel wire mesh frame serves as a cathode, wherein the carbon fiber suspension filler is connected in series by stainless steel wire ropes, and the carbon fiber suspension filler and the steel wire mesh frame are connected via an electrochemical workstation; S2, inoculating hydrolytic acidifying bacteria into the reactor, controlling the culture conditions, and taming the microorganisms in a microcurrent environment until a biofilm is formed on the carbon fiber suspension filler; S3. Input the wastewater to be treated into the reactor, control the treatment conditions, monitor the effluent results, and discharge it after it meets the standards.

2. A hydrolysis-acidification wastewater treatment process for enhancing extracellular electron transfer according to claim 1, characterized in that: The carbon fiber suspension filler in step S1 is prepared by the following steps: Select carbon fiber filaments with a diameter of 0.5-1.0 mm, wash the carbon fiber filaments, soak them in a hydrogen peroxide solution for activation, take them out and dry them to obtain pretreated carbon fiber filaments, immerse the pretreated carbon fiber filaments in a coating solution, keep them for 10-20 minutes, take out the carbon fiber filaments, absorb the excess coating solution with filter paper, hang them in an oven and dry them for 2-4 hours until the coating layer is solidified, and after cooling, obtain carbon fiber suspension filler.

3. The hydrolysis-acidification wastewater treatment process for enhancing extracellular electron transfer according to claim 1, characterized in that: The culture conditions in step S2 are as follows: temperature is 30±2°C, pH is 6.5-7.5, and C:N:P is maintained at 100:(5-5.5):(1-1.2).

4. The hydrolysis-acidification wastewater treatment process for enhancing extracellular electron transfer according to claim 1, characterized in that: The microcurrent environment in step S2 is specifically as follows: the initial current is 1 mA, which gradually increases by 0.08-0.12 mA every 2 days until the final current is 5-5.4 mA, and the total acclimation period is no less than 30 days.

5. The hydrolysis-acidification wastewater treatment process for enhancing extracellular electron transfer according to claim 1, characterized in that: The specific processing conditions in step S3 are: the water flow rate is 0.4-0.6m 3 / h, maintain the hydraulic retention time at 18-24h, and adjust the current to 3-7mA through the electrochemical workstation.

6. The hydrolysis-acidification wastewater treatment process for enhancing extracellular electron transfer according to claim 2, characterized in that: The concentration of the hydrogen peroxide solution is 0.1-0.3 mol / L, the activation temperature is 60-70° C., and the activation time is 1-2 h.

7. The hydrolysis-acidification wastewater treatment process for enhancing extracellular electron transfer according to claim 2, characterized in that: The coating solution is prepared by the following steps: A1. Add iodine and magnesium bars into the reactor, keep the reaction solution slightly boiling, add hexyl bromide dropwise, and after the addition is complete, continue to add anhydrous ethanol solution containing thiophene dropwise. After the addition is complete, react for 24 hours, separate the organic layer with saturated ammonium chloride solution, dry it with anhydrous sodium sulfate, and collect 3-hexylthiophene by distillation; A2, 3-hexylthiophene and potassium polymetaphosphate were added to a reactor pre-filled with toluene solvent, and stirred and dissolved under nitrogen protection until completely transparent, azobisisobutyronitrile and butylated hydroxyanisole were added, the reactor was sealed, and the reactor was placed in an oil bath, heated to 70-80°C, and reacted for 24-36h. After the reaction was completed, the mixture was cooled to room temperature, poured into methanol for precipitation, and filtered to obtain a copolymer precipitate; A3. Add the copolymer to N,N-dimethylformamide, stir until dissolved, add nano titanium dioxide powder, use ultrasonic disperser for 20-30 minutes to evenly disperse, stir for 1-2 hours under magnetic stirring, filter, wash, place in a 60°C vacuum oven to dry to constant weight, and re-formulate with N,N-dimethylformamide to a coating solution with a concentration of 40-50%.

8. The hydrolysis-acidification wastewater treatment process for enhancing extracellular electron transfer according to claim 7, characterized in that: In step A1, the mass ratio of iodine, magnesium bar, hexyl bromide, thiophene and anhydrous ethanol is (0.2-0.3):(6.2-6.8):(50-52):(27.5-29):

200.

9. The hydrolysis-acidification wastewater treatment process for enhancing extracellular electron transfer according to claim 7, characterized in that: In step A2, the mass ratio of 3-hexylthiophene, potassium polymetaphosphate, toluene, azobisisobutyronitrile and butylated hydroxyanisole is (20-21.5):(12-14):100:(0.1-0.3):(0.05-0.07).

10. The hydrolysis-acidification wastewater treatment process for enhancing extracellular electron transfer according to claim 7, characterized in that: In step A3, the mass ratio of the copolymer, N,N-dimethylformamide and nano-titanium dioxide powder is (10-11):50:(2-2.5).

Citation Information

Patent Citations

  • Culture enrichment device and method for degrading DMAC electrochemical active bacteria

    CN112551680A

  • Electrode system and high-efficiency low-energy-consumption hydrolytic acidification coupling electro-catalysis device

    CN114735807A

  • Treatment method and system for enhancing nitrogen and carbon removal of refractory industrial wastewater

    CN118878082A

  • Electrolyte additive for lithium-ion battery and preparation method and application thereof

    EP4468436A2

  • Biomembrane electrode material based on special-shaped carbon fiber, and preparation method therefor and use thereof

    WO2022000364A1

Cited By

  • Microbial enhanced water treatment method based on carbon fiber filler

    CN120192017A

  • A microbial enhanced water treatment method based on carbon fiber filler

    CN120192017B

  • Hydrolysis acidification treatment process for printing and dyeing wastewater

    CN121494188A